STUDY OF MOLECULAR INTERACTIONS OF NH -MCM-41 IN PRESENCE OF NICOTINAMIDE (A HYDROTROPIC AGENT) IN ETHANOL FOR PARTIALLY SOLUBLE DRUGS 2 - Swagatika, Srabani; Kumar Dash, Suresh; Dash, Upendra Nath (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT A solution of NH 2 -MCM-41 (5 and 10 weight %) has been prepared by taking tetraethylorthosilicate as silica source and 3-amino propyltriethoxysilane as amine source. The samples were characterized by scanning electron microscopy, X-ray diffraction, and Fourier transform infrared. The density, viscosity, and conductance of NH -MCM-41 (5 and 10 weight %) have been measured in the concentration range of 40-140 ppm in ethanolic solution of hydrotropic agent nicotinamide at different temperatures ranging from 298.15 to 313.15 K at an interval of 5 K. The density and viscosity data have been analyzed for the evaluation of limiting apparent molar volume (V 2 Ï† 0 ), limiting apparent expansibility (E ), Falken-Hagen coefficient (a), and Jones-Dole coefficient (b). The conductance data have been analyzed by Shedlovsky method to obtain limiting molar conductance (Î› Ï† 0 ) and association constant (K A ). The thermodynamic parameters such as change in enthalpy (Î”H 0 ), entropy (Î”S 0 ), free energy (Î”G 0 0 ), and Walden product (Î› ) for the ion pair formation have been calculated from the value of ion association constant at constant temperature. The results have been discussed in terms of solute-solute; solute-solvent interactions. This investigation would give information regarding pharmacokinetics and pharmacodynamics of these drug carriers. Keywords: NH 2 -MCM-41, Ethanol, Apparent molar volume, Nicotinamide, Association constant. m 0 Î· 0